2015
DOI: 10.1007/s10502-014-9238-9
|View full text |Cite
|
Sign up to set email alerts
|

Destruction/reconstruction: preservation of archaeological and zoological research data

Abstract: Archaeology and zoology are fields in which data collection and analysis involve destruction. In this study we examine the results of 49 interviews with archaeologists and zoologists, focusing on researchers' discussions of internal or disciplinary norms and external factors affecting their attitudes and actions concerning preservation. We identified two categories of disciplinary practices: data collection and data management/recordkeeping as key to shaping attitudes and activities about preservation. Likewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…however, data in the social sciences and humanities are not collected digitally all the time. In archeology, the results of observational data can be more closely linked to the object, photographs, or videos 30 .…”
Section: Subject Coverage Of Research Data Repositoriesmentioning
confidence: 99%
“…however, data in the social sciences and humanities are not collected digitally all the time. In archeology, the results of observational data can be more closely linked to the object, photographs, or videos 30 .…”
Section: Subject Coverage Of Research Data Repositoriesmentioning
confidence: 99%
“…Despite the growth in research about data practices, sharing, and reuse, and advances in standards and practices through organizations such as the Research Data Alliance and Force11, few have studied the role of data archives in knowledge infrastructures. All too often, the data archive is a "black box" to which data are contributed and from which data are retrieved Borgman, Darch, Sands, Wallis, & Traweek, 2014;Force11, 2018;Mayernik, Wallis, & Borgman, 2013;Mayernik, Wallis, Pepe, & Borgman, 2008;Pasquetto, Randles, & Borgman, 2017;Research Data Alliance, 2018a;Wallis et al, 2013).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…In reality, even incoming collections can arrive with poor provenience documentation. Rebecca Frank and her colleagues (2015:151–152) found that archaeologists, who appreciate the destructive nature of archaeological excavation, still resist responsibility for the long-term preservation of archaeological data. One archaeologist in their study lamented that a lot of contextual information “only seems to exist in the heads of people,” whereas others worried about the long-term preservation of digitally collected provenience information.…”
Section: Ensure Accurate Provenience Informationmentioning
confidence: 99%